The Role of Financial Performance in Moderating the Impact of Good Corporate Governance on Corporate Social Responsibility - Muhammad Heru Naufal; Hersugondo Hersugondo (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
This study examines the effect of Good Corporate Governance (GCG) which is proxied by managerial ownership, institutional ownership, public ownership, and the board of commissioners on Corporate Social Responsibility (CSR) which is proxied by the ESG Disclosure score, and also examines the role of the moderating variable Financial Performance which is proxied by Tobin’s Q on the relationship between GCG and CSR towards companies listed on the Indonesia Stock Exchange (IDX). The sample data obtained is from 87 companies during the 2017-2021 period. The method used in model A is multiple linear regression, while the effect of the moderating variable in model B is tested by using multiple regression analysis. The results of model A show that managerial ownership and institutional ownership have a significant negative impact on CSR, but public ownership does not have any effect. Meanwhile, the board of commissioners has a significant positive impact on CSR. The analysis results of model B show that financial performance can moderate the negative relationship between GCG and CSR. These results can broaden knowledge and provide practical benefits for companies and the academic community in management, financial accounting, and marketing, especially regarding GCG and CSR activities.